MENINGKATKAN KEMAMPUAN PENALARAN MAHASISWA PAI DENGAN MODEL PEMBELAJARAN ARGUMENT DRIVEN INQUIRY (ADI) - Misuhetni Maisuhetni (Edu Global : Jurnal Pendidikan Islam, 2022)
This research was aimed to examine the gain of PAI students’ reasoning ability whose study under Argument Driven Inquiry (ADI) Learning Model. This research used One Group Preetest-Postest Design. The independent variable was Argument Driven Inquiry (ADI) Learning Model and dependent variable was students’ reasoning ability. The sample was conducted by random sampling method. Collecting data was conducted by an observation sheet and the reasoning ability test. The statistical method used was inferensial statistic with hypotheses testing used Normalized Gain. The result of this research showed that: (1) there was a gain of students’ reasoning ability whose study under Argument Driven Inquiry (ADI) Learning Model; (2) the N-Gain score was 0,31 with medium category; (3) students showed positive attitude when study under Argument Driven Inquiry (ADI) Learning Model.